How Do Collective Efficiency and Norms Influence the Social Resilience of Iranian Villagers Against the COVID-19? The Mediating Role of Social Leadership - Valizadeh, Naser; Ghazani, Ezatollah; Akbari, Morteza; Shekarkhah, Javad (Frontiers in Public Health, 2022)
The main purpose of the present research was to investigate the effects of collective efficacy and norms on the social resilience against COVID-19 with the mediating role of social leadership. To this end, a cross-sectional survey was carried out in the Kerman and Fars provinces of Iran. Finally, 206 villagers were selected as the sample for collecting the required information. The research tool was a close-ended questionnaire whose validity and reliability were evaluated and confirmed. The results of testing direct hypotheses using structural equation modeling revealed that collective efficacy, social leadership, and norms had significant positive effects on social resilience against the COVID-19 pandemic. Comparison of the standardized effects demonstrated that collective efficacy is the most powerful predictor of the social resilience of villagers. Furthermore, testing indirect (mediation) hypotheses revealed that social leadership can successfully mediate the effect of collective efficacy on social resilience against COVID-19. Investigating the moderated indirect hypotheses showed that governmental supports moderated the effect of collective efficacy on social resilience. Taken together, the independent variables could account for 62 percent of social resilience variance change. In the end, the practitioners, decision-makers, and interveners of COVID-19 management programs in rural communities were provided with some applicable recommendations to be able to foster social resilience against COVID-19.